Recreation, event, and tourism businesses start-up and sustainable operations - Pfister, Robert E.; Tierney, Patrick T. (Human Kinetics, 2009)
Recreation, Event, and Tourism Businesses: Start-Up and Sustainable Operations uncovers the keys to business success in the commercial recreation, event, and tourism sector--one of the fastest-growing segments in the tourism and recreation industry. Until now, students, professors, and professionals interested in this growing industry have been limited to general business or basic recreation texts. With Recreation, Event, and Tourism Businesses, Robert E. Pfister and Patrick T. Tierney have combined their expertise both as business owners and professors to offer a comprehensive and industry-specific textbook and step-by-step guide for business start-up. Written from both entrepreneurial and operations management perspectives, the book provides a practical overview of the recreation, event, and tourism (RET) field and the business planning process. A new conceptual model of the RET industry is presented and related to existing models. It explains how the industry works and examines the key components of commercial RET businesses. It also describes how companies are started, operated, and managed, including information on service issues, risk management, finance, and marketing. It provides examples of how RET businesses can be operated in a more sustainable, environmentally friendly manner. Many of the topics covered in this book are key learning components for people wishing to obtain certification as a commercial recreation professional from organizations such as the Resort and Commercial Recreation Association and Meeting Professionals International. Recreation, Event, and Tourism Businesses provides students with practical business concepts and content that link to the core principles of the RET field so they'll be professionally prepared to deliver appropriate services. They'll explore contemporary management practices while discovering the diverse career opportunities available in the RET industry. The following are other student-friendly features: Tech Applications describe various specialized technologies and their applications to the RET industry; Multinational case studies provide detailed analysis of recreation businesses, with discussions of start-up, services provided, marketing, revenues and costs, management challenges, and future plans; Green Tips provide practical suggestions for making specific elements of an RET business more environmentally responsible; Spotlight On sections highlight the profiles of successful entrepreneurs and their locations, backgrounds, and professional advice or plans for the future. Recreation, Event, and Tourism Businesses also presents new professionals and potential business owners with clear, easy-to-read directions for developing and writing a business plan. A student or entrepreneur can use chapters in the book to develop sections of a business plan as a semester-long project or a serious business endeavor. The book's business profiles and case studies serve as examples to follow when working on the plan and help readers gain insight into how businesses are planned, started, and funded. It lays out important strategies for starting a business and shares best practices based on successful RET businesses. The authors also share advanced management and marketing strategies based on their experience as business owners. The key concepts of liability, marketing, finance, and operational standards are not simply academic concepts but practices honed by the authors' 20-plus years of experience in operating recreation and tourism businesses. A unique feature of the book is documenting and demonstrating how recreation, event, and tourism businesses can move toward a more environmentally and socially sustainable future. While it does include discussions of the traditional meaning of sustainability, generating sufficient profit to propel growth, it also presents the modern evolving concept of "triple bottom-line" accounting. It describes the need to consider environmental and social sustainability factors as well as profit when evaluating the success of the firm, and it explains how to include these considerations in the evaluation process. It also shows how environmental management, green business practices, and green technology are important for RET businesses. Green Tips throughout the book offer guidance in environmentally friendly and sustainable business practices. The book presents examples of how expenditures in green technology and practices can produce short- and long-term financial gains. Topics include green building certification, leave no trace principles, and operating carbon neutral. Finally, it shows how an RET business can measure its progress in a sustainability report. Recreation, Event, and Tourism Businesses: Start-Up and Sustainable Operations provides a comprehensive view of the industry, offering new insights for current practitioners and thorough preparation for students seeking careers in the recreation, event, and tourism industry. With its specific focus, it is the only text for current RET theories and practical management applications. Entrepreneurs and employees alike will find this practical guide offers the business knowledge, practical tips, resources, and valuable insights to guide their careers in the exciting and rewarding recreation, events, and tourism industry